Strategic alignment of business operations with the 2030 Agenda's SDGS: A case study of Químea Environmental Solutions (Research, Society and Development, 2026)
This study aims to expand knowledge on how companies can align their actions with the Sustainable Development Goals (SDGs) declared in the 2030 Agenda. The article's primary objective is to evaluate the alignment of services provided by Químea with the SDGs and their targets, classifying their interconnections to demonstrate how daily operations foster sustainable development. The methodology employed was qualitative in nature. Data collection occurred through a bibliographic review, analysis of information from the company's institutional website and interactive application, as well as by conducting semi-structured interviews with internal stakeholders. As a result, the analysis identified actions aligned with 14 out of the 17 SDGs in the 22 services offered, as declared in the 2030 Agenda. Notably, SDG 12 (Responsible Consumption and Production) and SDG 6 (Clean Water and Sanitation) were the most significant in terms of recurrence. Regarding categorization, 34 alignments were identified across the 25 distinct targets, with 23 direct and 11 indirect. All these alignments can be visualized in a relational figure, specifically developed to facilitate the comprehension of these linkages. In summary, the services provided by the company to its clients are intrinsically articulated with the SDGs, forming a multifaceted approach and a guide for a more equitable and environmentally responsible future. Thus, this study represents a concrete contribution to understanding how companies can align their actions with the 2030 Agenda.